2022
DOI: 10.1021/acs.jafc.2c05255
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coated Sulfur Nanoparticles Suppress Fusarium Disease in Field Grown Tomato: Increased Yield and Nutrient Biofortification

Abstract: Little is known about the effect of nano sulfur (NS) under field conditions as a multifunctional agricultural amendment. Pristine and surface coated NS (CS) were amended in soil at 200 mg/kg that was planted with tomato (Solanum lycopersicum) and infested with Fusarium oxysporum f. sp. lycopersici. Foliar exposure of CS (200 μg/mL) was also included. In healthy plants, CS increased tomato marketable yield up to 3.3∼3.4-fold compared to controls. In infested treatments, CS significantly reduced disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…lachrymans, and Colletotrichum spp., can be controlled by nanoparticles of Cu, ZnO, MgO, FeO, and Ag. Furthermore, they may regulate the active chemicals that are discharged when employing nanoparticles as carriers, which improves absorption, promotes the availability of water and nutrients, and diminishes their adverse impacts on the environment [147,148]. With their long shelf lives, tailored absorption, dispersion, minimal soil dissolution, and toxic consequences, nano-pesticides effectively prevent plant diseases and promote plant development [149].…”
Section: Effect Of Nano-fertilizers On Plant Diseasementioning
confidence: 99%
“…lachrymans, and Colletotrichum spp., can be controlled by nanoparticles of Cu, ZnO, MgO, FeO, and Ag. Furthermore, they may regulate the active chemicals that are discharged when employing nanoparticles as carriers, which improves absorption, promotes the availability of water and nutrients, and diminishes their adverse impacts on the environment [147,148]. With their long shelf lives, tailored absorption, dispersion, minimal soil dissolution, and toxic consequences, nano-pesticides effectively prevent plant diseases and promote plant development [149].…”
Section: Effect Of Nano-fertilizers On Plant Diseasementioning
confidence: 99%
“…For the field experiment, the experimental site was established at the Connecticut Agricultural Experiment Station’s Lockwood Farm located in Hamden, Connecticut. The soil was previously characterized as a Cheshire Fine Sandy Loam with a pH of 5.9 . Microplots were established in spring 2023 with rows 0.9 m wide and spaced 6 m apart.…”
Section: Methodsmentioning
confidence: 99%
“…The soil was previously characterized as a Cheshire Fine Sandy Loam with a pH of 5.9. 39 Microplots were established in spring 2023 with rows 0.9 m wide and spaced 6 m apart. The plots were fertilized with 112 kg/ha of 10−10− 10 NPK, covered with black plastic mulch, and irrigated using drip tape.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 61 In fact, in plants nano-sulfur activity is known to be similarly influenced; for example, Wang et al demonstrated that soil application of 200 mg L −1 of stearic acid coated (1–2 wt%) nano-sulfur significantly reduced Fusarium infested tomato plants compared to the uncoated nanomaterial. 57 …”
Section: Nano-sulfur: Diverse Uptake Pathways In Plantsmentioning
confidence: 99%